A critical introduction to psychology - Beshara, Robert K. (Hauppauge : Nova Science Publishers, 2020)
"A Critical Introduction to Psychology is the first scholarly book, in which fifteen critical psychologists analyze chapters from popular Introduction to Psychology textbooks. In their critiques of mainstream (Euro-American) psychology, the authors of this edited volume also envision a pluriversal, transdisciplinary psychology, which is inclusive of critical voices from all over the world"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.